Management Of Training Systems In Improving Hr Competency In Oil Palm Plantation Companies PT. Kayung Agro Lestari, And PT. Austindo Jaya Nusantara Agri Siais - Kresnanda, Surya; Abin Syamsudin M, Tb.; Ratnawulan, Teti; Syaodih, Cahya (Publisher Cv. Inara, 2022)
Oil palm plantations are long-lived plants and require special management with special land. HR competencies need to be continuously improved, given the lengthy business processes that require large funds and the increasingly fierce competition in the oil palm plantation business. Education and training are important entities in managing the learning and growth process for employees in order to improve competence and achieve company goals and win the competition. A good management of the education and training system will result in an effective training process to improve the competence of human resources, which will enable oil palm plantation companies to find productive jobs. This study aims to describe and analyze the development of management training systems in improving the competence of human resources at PT Sahabat Mewah dan Makmur, PT Kayung Agro Lestari, and PT Austindo Nusantara Jaya Agri Siais. The research method used is descriptive with a qualitative approach, collected through 1) observation, 2) interviews, 3) documentation studies. The results showed that the hypothetical model of the training and education management system in improving the competence of human resources is influenced by the administrative management process, the influence of strategic decision makers, and either instructors or mentors appointed for the training process. The recommendation from this research is that special efforts are needed to build the quality of educators in the education and training system because the quality factor of educators, both instructors and mentors, has a big influence. It is also necessary to pay attention to the unavoidable natural and environmental aspects, and to make adjustments to the education and training process based on the natural situation and the environment in which the plantation is located. In addition, it is necessary to build communication with various parties outside the education and training to meet the needs of many parties whose decisions directly affect the implementation of education and training.